Chapter 15 Conclusions - Thomson, Harriet (Taylor & Francis, 2018)
We began this book with the aim of providing the first global and comparative perspective on energy vulnerability, in order to advance debates on the systemic processes and conditions that (re)produce domestic energy deprivation. By bringing together 13 chapters that cover 14 countries in total, the volume provides the first instance where such divergent contexts are brought together to discuss energy vulnerability in one common space. In this concluding discussion, we look across the range of contributions and draw out some overarching lessons, policy implications and future research directions.